Legal Politics of Indonesian Environmental Management: Discourse between Maintaining Environmental Sustainability and Economic Interests - Ega Rijal Mahardika; Muhammad Azhary Bayu (Indonesian Journal of Environmental Law and Sustainable Development, 2022)
Environmental management in Indonesia has undergone various policy changes, in addition to overlapping interrelated legal regulations. Environmental management in addition to dealing with aspects of nature conservation, is also related to economic aspects, investment, and sustainable development. On the one hand there is an interest in preserving nature and protecting nature as it should be, but on the other hand there is a shift in interests, especially with regard to investment and economic interests. This study aims to analyze the political direction of environmental management law in Indonesia.